REDESIGN OF LICENSING IMPLEMENTATION TRYING TO IMPROVE THE REGIONAL INVESTMENT ECOSYSTEM - Okta Ainita (Law Faculty of Universitas Bandar Lampung, 2021)
In the current practice in Indonesia, the government places licensing as a form of obligation that must be fulfilled by business actors to be able to carry out business activities legally (license approach). The complicated problem of doing business in Indonesia is caused by so many regulations (over-regulated) in the licensing sector whose substance is not harmonious, overlaps, and even contradicts one another. Such regulations create a long and complicated licensing system that results in the investment climate in Indonesia becoming ineffective, inefficient, and not providing legal certainty. The working mechanism of business services in Indonesia is considered to take a long time, is not transparent, is not informative, has limited service facilities and infrastructure so that which requires high costs. The urgency of licensing redesign is motivated by the weak investment competitiveness and growth of the private sector in Indonesia. The big agenda of building a productive investment-based economy is threatened to run aground or move slowly if all the blockages in the administrative and policy spheres are not carried out by reconstruction. Policy improvements to simplify business licensing, which are carried out in a relatively short time, uncomplicated procedures, and low costs for establishing, operating, and developing businesses are expected conditions. By implementing risk-based regulations as a reference for determining the type of business licensing accompanied by the implementation of inspections for effective control, will simplify the business licensing mechanism and will ultimately provide economic, social, and environmental benefits.